2021
DOI: 10.2106/jbjs.cc.21.00088
|View full text |Cite
|
Sign up to set email alerts
|

Suture Fixation of a Pediatric Pelvic Ring Injury

Abstract: Case: A 2-year-old male child presented as a polytrauma after having been run over by a motor vehicle. His orthopaedic injuries included a pelvic ring injury, a displaced subtrochanteric femur fracture, and a clavicle fracture. His pelvic ring injury ultimately required open reduction with suture fixation after failure of closed management. Conclusion: Pelvic ring injuries are relatively uncommon in young children, and even more rarely do they require s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, more recent studies have shown that children left with pelvic asymmetry do not remodel as well as previously thought and can develop numerous complications with common complications including leg length discrepancies, scoliosis, and low back pain [1,3,5,6]. As such, surgeons have described fixation approaches in young patients with pelvic fractures, including suture-based fixation [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies have shown that children left with pelvic asymmetry do not remodel as well as previously thought and can develop numerous complications with common complications including leg length discrepancies, scoliosis, and low back pain [1,3,5,6]. As such, surgeons have described fixation approaches in young patients with pelvic fractures, including suture-based fixation [7].…”
Section: Discussionmentioning
confidence: 99%